Shear Resistance Evolution of Geogrid Reinforced Expansive Soil Under Freeze–Thaw Cycles - Zhongnian Yang; Jia Liu; Runbo Zhang; Wei Shi; Shaopeng Yuan (Applied Sciences)
Expansive soils have significant characteristics of expansion by water absorption, contraction by water loss. Under the freeze–thaw (F-T) cycles, the engineering diseases are more significant, and the serious geotechnical engineering incidents are induced extremely easily. The aim is to investigate the mechanical response characteristics of geogrid-reinforced expansive soils (GRES) under F-T cycles. Based on a series of large-scale temperature-controlled triaxial tests, influencing factors were considered, such as the number of F-T cycles, the geogrid layers, and the confining pressure. The results showed that: (1) Friction between the expansive soil and geogrid and the geogrid’s embedded locking effect indirectly provided additional pressure, limited shear deformation. With the increase in reinforced layers, the stress–strain curve changed from a strain-softening to a strain-hardening type. (2) Elastic modulus, cohesion, and friction angle decreased significantly with increasing number of F-T cycles, whereas dynamic equilibrium was reached after six F-T cycles. (3) The three-layer reinforced specimens showed the best performance of F-T resistance, compared to the plain soil, the elastic modulus reduction amount decreases from 35.7% to 18.3%, cohesion from 24.5% to 14.3%, and friction angle from 7.6% to 4.5%. (4) A modified Duncan–Zhang model with the confining pressure, the F-T cycles, and the geogrid layers was proposed; the predicted values agreed with the measured values by more than 90%, which can be used as a prediction formula for the stress–strain characteristics of GRES under freeze–thaw cycling conditions. The research results can provide important theoretical support for the practical engineering design of GRES in cold regions.